TRIGGERING FACTORS, RISKY BEHAVIORS AND RESILIENCE OF STREET CHILDREN IN GONDAR CITY, NORTH WEST ETHIOPIA SIMEGN SENDEK YIZENGAW1 AND ASFAW GETNET GEBIRESILUS2 1,2 Lecturer, Psychology Department, College of Social Sciences and Humanities, University of - yizengaw, simegn sendek; gebiresilus, asfaw getnet (Innovare Journal of Social Sciences, 2014)
ABSTRACT The main purpose of this study was to examine the triggering factors, risky behaviors and resilience of street children in Gondar city. One hundred ten street children were selected through purposive sampling technique. The data pertinent to the study was gathered through questionnaire and analyzed by using descriptive statistics (percentage, frequency, mean and standard deviation) and inferential statistics (independent tâ€“test and one way ANOVA). The result of the study revealed that children come to the streets for searching job, poverty, parental disintegration, peer pressure, family influence, city life attraction, parental use, school failure and following strangers in order of regularity. Regarding risk taking behaviors, males had statistically significant higher mean scores than females only in criminal acts; children â€˜of' the streets scored statistically significant higher mean than children â€˜on' the streets on the overall risk taking behavior including criminal acts, substance use and risk sexual practice. Furthermore, statistically significant difference were observed across the of seven to 10 years, 11-14 years and 15-18 years on the overall risky taking behavior, substance use and risk sexual practice. Generally majority of participants had moderate resilience: where females reported statistically significant higher mean score than males only on access to support and children 'on' the streets significantly higher than children 'of' the streets on the overall resilience, its dimensions and specific components like adaptability, self-efficacy, optimism, trust, tolerance of difference, social comfort, access to support and sensitivity. Â Keywords: street children, children â€˜on' the street, children â€˜of' the street, risky behaviors, resilience